O GeoGebra como recurso facilitador do ensino de funções de primeiro e segundo grau em matemática e cinemática em física - Pereira Júnior, Joel Lisboa (2023)
This work presents a proposal for using the GeoGebra software as a tool to facilitate interdisciplinarity between Mathematics and Physics in primary and secondary education in subjects related to affine and quadratic functions. The study was carried out with first-year high school students from a public military school in São José de Ribamar, Maranhão. The research involved practical activities and specific exercises using GeoGebra, and the results showed that students were able to use the software appropriately, indicating that its use had a positive impact on the teaching and learning process